The Indicators of Construction Land Suitability Assessment (CLSA) for Quality of Rural Life (QRL) in Mountain Areas - Zhu , Xiongbin; Srirangam, Sucharita; Mari, Tamilsalvi (MAJ - Malaysia Architectural Journal, 2023)
The global mountains cover about 1/4 of the surface, more than half of the population depends on water from mountain areass. Therefore, the construction of mountain areass is related to the global well-being. However, with the rapid expansion of rural construction land and unreasonable land layout, the ecological environment in mountain areass is deteriorating, and it has seriously affected the Quality of Rural Life (QRL). Construction Land Suitability Assessment (CLSA) is the premise of land selection and rational use. Although the research domain on CLSA has made significant progress in plain and urban areas, there is seldom work done for mountainous and rural areas, especially the factors affecting CLSA. Due to climate, terrain, cultural differences, the assessment factors must varied from plain areas. Therefore, the research aims to identifying the factors that affect the suitability of construction land and determining the indicators of CLSA from the perspective of improving QRL in mountain areass. Based on the theory of physical determinism, under the guidance of location theory and sustainable development theory, the study make a hypothesis that the QRL is affected by the spatial location indicators of villages. With document analysis method and theoretical research method to verify the relationship between CLSA and QRL, and deduced the 7 indicators(slope, slope direction, distance from water source, width of routes, distance from city, distance from cultivated land and aggregation degree of rural residential areas) for CLSA based on QRL in mountainous and rural areas. The outcomes can be developed as a toolkit for site selection of rural construction land. Finally, it is expected to mitigate the issues of the low QRL caused by a lack of rational land layout guidance and guide rational development and coordinate the contradiction between population growth and land resources shortage in mountain areas, and realize sustainable development of rural areas.